University management for institutional self-assessment with a formative nature of medical universities - Tamara Chaos Correa; Jorge García Batán; Jesús de Farit Rubio Méndez (Medisur)
Foundation: innovative universities are distinguished by their impact on the current challenges of modern society, where the progress of the university environment is crucial. Objective: argue the theoretical-practical foundations of university management for institutional self-evaluation with a formative nature of medical universities. Methods: a case study was carried out in Research in Health Systems and Services, with emphasis on university management processes, modeled from the structural-functional systemic method. Qualitative methods were used to reveal the arguments that support the sustainability of self-assessment in training processes. Results: the theoretical derivations on university management for institutional self-assessment with a formative nature of medical universities allow us to consider this process as a system, susceptible to being perfected by considering two subsystems, one prescriptive of the university community organizational context, and another contentive of the appropriation of the self-assessment process for self-regulation and accreditation purposes, which contribute to training sustainability. From the synergistic and recursive relationships in this system, the quality of responsibility for the transformation of the training process derives. Conclusions: university management as a process contributes to training sustainability in institutional self-assessment. It is a strategic tool to achieve process quality through continuous improvements. It is characterized by shared, contextualized commitment, the involvement of the actors in the process, collective and participatory responsibility, all conditions that favor educational influences.